Profile of urinary tract stone in Makassar, Indonesia - Sulaksono, Tommy; Syahrir, Syakri; Palinrungi, Muhammad Asykar (International Journal of Research in Medical Sciences, 2019)
Background: Urinary tract stone disease (urolithiasis) is still a significant health issue throughout the world. In Asia, regions with very high urolithiasis incidence stretch from Sudan, Saudi Arabia, United Arab Emirates, Pakistan, India, Myanmar, Thailand, Indonesia, and Philippines. Demographic and regional variations in cases of urolithiasis may provide clues to their etiology and prevalence. The aim of this study was to determine the characteristics of urolithiasis patients and their management in Makassar. Methods: This was a single centre retrospective descriptive study using data from patient medical records at Dr. Wahidin Sudirohusodo Hospital Makassar in 2015-2017. Patients’ demographic, clinical, and management characteristics were recorded. Results: From 1,166 urolithiasis patients, author found men were more dominant than women with ratio of 2.2: 1. Age distribution were more common in the range of 40-60 years (58.32%). The distribution of patients with high Body Mass Index (BMI) were relatively common included overweight 20.5% and obese 13.81%. The majority of cases were unilateral urolithiasis (89.28%), with stones were largely found in kidney (59.41%). Extracorporeal Shock Wave Lithotripsy (ESWL) was the method more commonly performed (48.13%) followed by lithotripsy. Conclusions: This study showed that urolithiasis were commonly found in the age group of 40-60 years, predominantly male, and high BMI were relatively common. The majority of cases were unilateral urolithiasis, mostly located in kidney. Urolithiasis were mostly managed by ESWL and lithotripsy.